Cyclicality in the Fiscal Policy of Nepal - Koirala, T.P. (NRB Economic Review, 2015)
This paper examines discretionary fiscal policy response to the business cycle of Nepal using annual time series ranging from 1975 to 2013. The Cyclically Adjusted Balance (CAB) of overall budget balance is utilized as a measure of discretionary fiscal actions and the output gap a measures of business cycles. Graphical depiction of the CAB accompanied with the output gap shows that the government of Nepal has been pursuing counter-cyclical fiscal policy in the post liberalization period and pro-cyclical in the pre-liberalization period. In line with the recent empirical finding that only counter-cyclical fiscal policy is capable in performing stabilization function, this paper found that the fiscal stimulus of the government of Nepal has also been adding aggregate demand during downturns (bad time) and withdrawing demand during upturns (good time) as envisaged by counter-cyclical discretionary fiscal policy. The counter-cyclicality as such is strong during 2000s whereas there is mild pro-cyclicality during the period 2011-13. For computing CAB, this paper assumes unitary elasticity of revenue with respect to output gap and zero expenditure elasticity with respect to output gap. The output gap has been estimated based on the trend component of the GDP using Kalman filter method. Factors like stronger institutions and sound macroeconomic policies might overcome recent pro-cyclicality of Nepal and allows room for counter-cyclical fiscal policy in the future. Similarly, the phenomenon of high fluctuations in the fiscal impulse over time indicates uncertain and inconsistent fiscal stance of the government. It demands for focus more on automatic stabilizers rather than more discretionary fiscal actions by broadening tax bases and social safety nets.